1984
DOI: 10.1128/iai.43.2.502-507.1984
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of alkali-soluble, water-soluble cell wall antigen of Coccidioides immitis with anti-Coccidioides immunoglobulin M precipitin antibody

Abstract: The alkali-soluble, water-soluble cell wall antigen of Coccidioides immitis (C-ASWS) mycelia and spherules was shown to react with anti-Coccidioides immunoglobulin M (IgM) precipitin antibody, both in the classical tube precipitin test and in the immunodiffusion assay for tube precipitin antibody (IDTP). The reactions obtained between C-ASWS and reference IgM precipitin antibody were identical to the reaction obtained when reference coccidioidin (CDN) was used. Definitive proof that C-ASWS extracts contain ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…The latter possessed two antigenic species not present in the mycelial preparation (or present in concentrations too low to be detected by twodimensional immunoelectrophoresis). Cox et al (7) have recently added to the information indicating that antigen 2 has reactivity conforming to the ID-TP antigen, indicating, as did Collins et al (3), that this antigen is associated with the cell wall. Cole et al (4) demonstrated the presence of antigen 2 in the walls of arthroconidia and spherules.…”
Section: Discussionmentioning
confidence: 94%
“…The latter possessed two antigenic species not present in the mycelial preparation (or present in concentrations too low to be detected by twodimensional immunoelectrophoresis). Cox et al (7) have recently added to the information indicating that antigen 2 has reactivity conforming to the ID-TP antigen, indicating, as did Collins et al (3), that this antigen is associated with the cell wall. Cole et al (4) demonstrated the presence of antigen 2 in the walls of arthroconidia and spherules.…”
Section: Discussionmentioning
confidence: 94%
“…Solid-phase immunoadsorption was used to isolate the antibody fractions reactive with the purified 120-kDa TP-Ag from a pool of five ID-TP-positive patient serum samples used in the TP assay of this same antigen in an earlier report (24). Coupling of antigen to CNBr-activated Sepharose 4B (Pharmacia Fine Chemicals, Piscataway, N.J.) and the subsequent washing procedure were conducted as reported by Cox and coworkers (15). The gel was transferred to a column (0.8 by 15 cm) and equilibrated with wash buffer (phosphate-buffered saline [PBS; pH 7.4] containing 0.15 M NaCl and 0.005% [wt/vol] thimerosal).…”
Section: Methodsmentioning
confidence: 99%
“…We also show that reactivity of the antigen with serum samples from patients with coccidioidomycosis is retained after pronase digestion or heating (100°C, 5 min) but is lost after periodate oxidation. Examination of the carbohydrate composition of the TP antibody-reactive antigen (TP-Ag) by gas chromatography-mass spectroscopy revealed 3-0-methylmannose (3-0-MM), a sugar that was previously shown to be a component of immunoreactive fractions of C. immitis (3,15,17,28,(35)(36)(37) and possibly unique to this pathogen among the systemic fungal pathogens (3,37). In this report, we also further examine the serologic reactivity of the 120-kDa TP-Ag and, in particular, the significance of 3-0-MM in precipitin binding to this macromolecule.…”
mentioning
confidence: 99%
“…44 Another protein, Antigen 2 (Ag2), was first identified in 1978 by two-dimensional immunoelectrophoresis (IEP) from the crude antigen preparations coccidioidin and spherulin, 45 and also found in the alkali-soluble, water-soluble mycelial and spherule extracts. 46 Ag 2 was not sequenced until 1996. 47 A parallel antigen discovery of the prolinerich antigen (PRA) was identified from a toluene spherule lysate.…”
Section: Application Of Proteomic Analysis To Fungal Systemsmentioning
confidence: 99%